2005
DOI: 10.1108/01439910510593965
|View full text |Cite
|
Sign up to set email alerts
|

Advances in tactile sensors design/manufacturing and its impact on robotics applications – a review

Abstract: PurposeReviews the benefits and potential application of tactile sensors for use with robots.Design/methodology/approachIncludes the most recent advances in both the design/manufacturing of various tactile sensors and their applications in different industries. Although these types of sensors have been adopted in a considerable number of areas, the applications such as, medical, agricultural/livestock and food, grippers/manipulators design, prosthetic, and environmental studies have gained more popularity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
66
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 46 publications
0
66
0
3
Order By: Relevance
“…When lifting a fragile grasp or holding a soft tissue and in other precision tasks, primarily the fingertips are used for contact. The precision grasp has advantages such as enabling better control of contact force and motion of object, but it is also less stable than the power grasp [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…When lifting a fragile grasp or holding a soft tissue and in other precision tasks, primarily the fingertips are used for contact. The precision grasp has advantages such as enabling better control of contact force and motion of object, but it is also less stable than the power grasp [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the risk of accidental cutting of the surrounding veins or arteries that are embedded in the tissues can lead to serious complications. Due to these problems, the loss of tactile sensing has proven to be a serious issue and has been the target of extensive research [16][17][18][19][20] . Some of the main previous research activities on this topic are presented below.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the necessity to sense the contact-force and mechanical properties of objects such as stiffness has particular importance in medical applications of the robotic hand in general and the development of surgical robot or telesurgery systems. It has been demonstrated that automation technology with artificial sensory can assist surgeons in minimal access treatment by enabling the benefits of steady tool motion through difficult access [3,5,9] .…”
Section: Introductionmentioning
confidence: 99%